Pregnant women with epilepsy in a developing country - Kochen, Sara Silvia (2011)
This is the first prospective study carried out in Argentina and Latin America to provide the impact of epilepsy throughout the childbearing years life of women, and pregnancy outcome in a population of pregnant women with diagnosis of epilepsy and antiepileptics drugs (AEDs). Ninety-four women were studied prospectively at the Epilepsy Center, the largest in Argentina. Of the 94 women examined in this study only 10% planned their pregnancy and received folic acid before conception. More than half of women in our study were on monotherapy, with the most frequently prescribed drugs being carbamazepine and valproic acid. In all, 90.4% of the women had a normal pregnancy and delivery. There were 8.5% spontaneous abortions. Major congenital malformations (MCM) was detected in 10.6% of newborns at birth; in the general population it varies between 1.6-3.2%. The results from this study are helpful in the highlighting correct gaps in knowledge in this population group. © Kochen et al.